When management is built as a team: participative management in business units of a mass consumer goods company (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
Participative Management is a management style in which organizational leaders consider the opinions and ideas of subordinates to aid in decision-making, fostering commitment and motivation to improve processes and achieve objectives. Therefore, the purpose of this research is to analyze the Participative Management model as a management tool in the business units of a mass consumer goods company in the state of Lara during 2024. This descriptive field study, employing a quantitative approach, involved administering two Likert-scale questionnaires to a selected sample of 82 individuals from the company's strategic, tactical, and operational levels. The results showed that the elements and characteristics of the participative model are present in all three business units, demonstrating a generally moderate level of participation among employees, considering their opinions and ideas to contribute to achieving objectives. The aim is to contribute to staff training and development programs to strengthen decision-making and improve the social and economic symbolic reward system in order to boost staff motivation and commitment to contributing new ideas in the pursuit of continuous improvement.
Keywords: participatory; management; decision making